Answer:
yes the small A. is equally to the big A. even though it is smaller and moved away from the big A.
Hope this helped!
Brainliest?
Answer:
(-1,6)
Step-by-step explanation:
The missing part of this question is the system given as;
![-c+2d=13](https://tex.z-dn.net/?f=-c%2B2d%3D13)
![-9c-4d=-15](https://tex.z-dn.net/?f=-9c-4d%3D-15)
We solve for c in the top equation to get:
![c=2d-13](https://tex.z-dn.net/?f=c%3D2d-13)
Substitute
into the bottom equation to get:
![-9(2d-13)-4d=-15](https://tex.z-dn.net/?f=-9%282d-13%29-4d%3D-15)
Expand to get:
![-18d+117-4d=-15](https://tex.z-dn.net/?f=-18d%2B117-4d%3D-15)
Group similar terms to get:
![-18d-4d=-15-117](https://tex.z-dn.net/?f=-18d-4d%3D-15-117)
![-22d=-132](https://tex.z-dn.net/?f=-22d%3D-132)
![d=6](https://tex.z-dn.net/?f=d%3D6)
Put
into
to get:
![c=2*6-13](https://tex.z-dn.net/?f=c%3D2%2A6-13)
![c=12-13=-1](https://tex.z-dn.net/?f=c%3D12-13%3D-1)
The solution is (-1,6)
Answer:
Where is the picture?
Step-by-step explanation:
Have a great day
Step 1: Set the two equations equal to each other and solve for x.
3x -5 = 6x - 8
3x + (-5+5) = 6x -8 + 5
(3x - 6x) = (6x - 6x) - 3
-3x/-3 = -3/-3
x = 1
Step 2: To solve for y take one of the given equation of your choice (for the purpose of this explanation I will only do y = 3x - 5) and replace x with 1, then solve for y
y = 3(1) - 5
y = 3 - 5
y = -2
(1,-2)
Check:
-2 = 3(1) - 5 ---> - 2 = -2
-2 = 6(1) - 8 ---> -2 = -2
Hope this helped!